Service delivery and the role of clinical pharmacists in UK primary care for older people, including people with dementia: a scoping review - Alice Burnand; Abi Woodward; Vladimir Kolodin; Jill Manthorpe; Yogini Jani; Mine Orlu; Cini Bhanu; Kritika Samsi; Victoria Vickerstaff; Jane Wilcock; Jane Ward; Greta Rait; et al. (BMC Primary Care)
Abstract Objective As populations age globally, there is increasing prevalence of multiple long-term conditions, such as dementia, leading to many challenges. The burden on health and care services, economic pressures, and the necessity for innovative policies to better support older people and people with dementia becomes paramount. This review explores how clinical pharmacists working in UK primary care support older people and people with dementia. Design Scoping review. Method This review was conducted following the framework for scoping reviews in accordance with the Joanna Briggs Institute (JBI) methodology. The search of Scopus, EMBASE, CINAHL, Web of Science, PsycINFO, and Cochrane was initially conducted in September 2022, and updated in August 2024. Searches included literature exploring the landscape of clinical pharmacy services for older people in the UK, focusing on roles and services delivered, perceptions, and experiences. Results A total of 30 articles were included. These detail the multifaceted responsibilities of clinical pharmacists in primary care for older people. Stakeholder perspectives, including healthcare professionals and patients, emphasised the positive outcomes of clinical pharmacist involvement, from reducing other practitioners’ workloads to improving patient safety. However, communication gaps, concerns about competence from other healthcare professionals, and the need for clear role definitions emerged as challenges. Research focused on the experiences of underserved groups, such as people with dementia or from minority ethnic backgrounds, is lacking. Conclusions and implications The review enhances our understanding of the primary care clinical pharmacist service in the UK and identifies gaps in evidence, emphasising the need for empirical studies on the experiences of older people with cognitive impairment and those from minority ethnic backgrounds. It provides insights into what makes an effective clinical pharmacist service, such as training and communication, which may help to inform international policy and practice and improve service provision globally.